A10.13 Identification of Immunophenotypic Signatures in Peripheral Blood of Multiple Sclerosis Patients by Multiparametric Flow Cytometry. (25th February 2013) - Schulte-Wrede, Ursula; Rosche, Berit; Grün, Joachim R; Radbruch, Andreas; Grützkau, Andreas
Abstract : Background: Multiple Sclerosis (MS) is a chronic inflammatory and demyelinating disease of the CNS with unknown aetiology until now. CD4+ T helper (Th) 1 cells, proinflammatory Th17 cells, CD8+ T cells, B cells, natural killer (NK) cells and denritic cells (DC) are accepted to play in important role in pathogenesis of disease. Lymphocytes of the peripheral blood from multiple sclerosis (MS) patients are characterised by proinflammatory function but robust cell surface markers to distinguish patients from controls are not available until now. Methods/Results: In this study we analysed frequency and phenotype of blood cell subsets by multicolour staining including up to 50 different monoclonal antibodies that allowed detecting 894 parameter combinations per sample, including 99 control parameters. Relative event numbers, absolute cell numbers and relative fluorescence intensities of all fluorochromes were compared between 10 patients with a clinically isolated syndrome (CIS) or early relapsing-remitting MS (RRMS) and 10 healthy age- and sex-matched controls and were analysed in a semiautomatic manner. Statistical significant results in expression profile between both groups were found involved receptors in inflammation (CD119, CD62L, CRTH2) on cells of adaptive and also innate immunity (Welch t-test < 0.05). Conclusions: The results identify a MS specific profile of peripheral blood leukocytes by a multiparametric cytometric approach. Thus, the large-scale immunophenotyping is appropriate tool to identify new disease relevant leukocyte subtypes and receptors and may have implications for diagnosis, pathophysiological understanding and therapy-monitoring of patients with MS and other autoimmune diseases.